Integrasi Sistem Informasi Manajemen dan Prinsip Pendidikan Islam di Universitas Bahaudin Mudhary (UNIBA) Madura - Ulya, Nadziratul; Mughayyirah, Yuniar; Mubarok, Imam Anas (Ulumuna: Jurnal Studi Keilsman, 2025)
This research discusses the planning and organizing stages in the implementation of Management Information Systems on campus. The results of the research confirm that careful planning, involving all related parties such as lecturers, students, and rectors is very important for the success of the implementation of Management Information Systems. Needs analysis that includes the types of data to be managed and the determination of the budget for hardware, software, and technical training is also considered crucial. Furthermore, the organizing stage that includes the formation of a cross-departmental implementation team and the arrangement of clear operational procedures greatly determines the smoothness of the implementation process. This study extends the findings of previous studies by highlighting the importance of data protection and access rules in Management Information Systems, aspects that are often overlooked in previous studies. These findings provide practical guidelines for schools in planning and organizing the implementation of Management Information Systems effectively and safely .